2006
DOI: 10.1159/000098029
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Pictures Revisited: Long-Term Changes in Repetition Priming, Relation to Skill Learning, and the Role of Cognitive Resources

Abstract: Background: Whereas age-related declines in declarative memory have been demonstrated in multiple cross-sectional and longitudinal studies, the effect of age on non-declarative manifestations of memory, such as repetition priming and perceptual skill learning, are less clear. The common assumption, based on cross-sectional studies, is that these processes are only mildly (if at all) affected by age. Objective: To investigate long-term changes in repetition priming and age-related differences in identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…Our results suggest that reconsolidation processes may operate best when an observer has a stronger original memory to rely on, as it is better able to assimilate newly encountered information. This is consistent with previous research, which has shown that after an initial exposure with a line drawing of a fragmented object, less information is needed to correctly identify that same object during a future test (Kennedy et al 2007).…”
Section: Clarifying Integration Mechanisms In Memorysupporting
confidence: 92%
“…Our results suggest that reconsolidation processes may operate best when an observer has a stronger original memory to rely on, as it is better able to assimilate newly encountered information. This is consistent with previous research, which has shown that after an initial exposure with a line drawing of a fragmented object, less information is needed to correctly identify that same object during a future test (Kennedy et al 2007).…”
Section: Clarifying Integration Mechanisms In Memorysupporting
confidence: 92%
“…This hypothesis was tested in the present study by assessing priming for unfamiliar objects at four different delays: subjects were tested for one set of items encoded immediately before the test phase and for a second set of items encoded either 20 min, 90 min, or 1 week before the test phase. In addition, the present study tested whether priming in older adults decreases more rapidly over time than in young adults, as has been suggested by some studies (Kennedy et al, 2007; Wiggs, Weisberg, & Martin, 2006; but see Mitchell, Brown, & Murphy, 1990 for a similar decrease in young and older subjects).…”
mentioning
confidence: 84%
“…In summary, basic repetition effects on both behavior and brain activation appear to be largely preserved with age, although these effects may be numerically smaller or not as long lasting (Wiggs et al 2006). For example, Kennedy, Rodrigue, and Raz (2007) found that both young and old adults showed priming effects for fragmented pictures on an immediate test, but only young adults retained these benefits at a five-year followup test (see the section on motor learning for similar findings in a mirror-writing task (Rodrigue et al, 2005)).…”
Section: Introductionmentioning
confidence: 98%